Clowns, buffoons and the killing laugh: An investigation of the Clandestine Insurgent Rebel Clown Army’s (CIRCA) power to disrupt and provoke through joy and humour - Hilary J Ramsden (The European Journal of Humour Research, 2015)
This essay offers an experiential account of the development of “rebel clowning” as a practice that emerged in the context of the anti-globalisation movements in the UK, bringing together the ancient art of clowning and more recent practices of non-violent direct action. The essay traces the legacies of rebel clowning, outlines the tactics and strategies that comprise its humour, and analyses key activist moments in its trajectory in the first decade of the 21st century. By inserting the logic of clowning into the activist realm, the essay argues, the tired binary between protester and authority, or activists and their opponents, is shaken and cheerfully disrupted.